Investigating English in Multilingual Contexts Online: Identity Construction in Geotagged Instagram Data - Mohr, Susanne (Frontiers in Communication, 2022)
Tourism discourse, referring to communication in tourism as global industry, contributes to the creation of tourist spaces, where space is a social and affective construct as opposed to place as a geographical one. Tourists and hosts are part of these spaces and form them with their language practices, both offline and online. This article presents a case study of tourism discourse related to Zanzibar on Instagram, focusing particularly on linguistic repertoires, the role of English in them and language choices as well as their implications for identity construction. A central issue, in line with discourse-centred online ethnography, is the comparison of the digital data with previously collected data from the physical tourist space. Theoretically and methodologically, the concept of (linguistic) transnationalism is central for the study, which uses geotags and hashtags as means of data retrieval and framework of analysis to further this concept.